ENTERPRISE RISK MANAGEMENT (ERM) SEBAGAI SUATU PROSES DAN SISTIM DALAM MANAJEMEN RISIKO - Muh. Ruslan Abdullah (MUAMALAH, 2014)
ISO 31000 provides an internationally recognized benchmark for the design and implementation of ERM framework for risk management. The ISO 31000 approach to developing and implementing ERM and compatible with other approaches, but it is the first standard to provide a complete and practical solution. Components of a comprehensive ERM framework and practical described. Each organization must determine for themselves how the components of the context of ISO ERM framework should be integrated into their organization to achieve an ERM framework that will be comprehensive in scope and practical for organizations.